¡Pásale!: Gaining Entrance to Conduct Research and Practice With Recent Hispanic Immigrants: Lessons Learned From the COPAL Study - Daniel Wood Soto; Jennifer B. Unger; Monica Pattarroyo; Alan Meca; Juan Andres Villamar; Maria Fernanda Garcia; Seth J. Schwartz (Frontiers Media S.A., 2022)
Given the rapidly changing political rhetoric and policies concerning immigration, and the likely impact of this rhetoric on immigrants' adjustment, it is essential to understand the experiences of recently arrived immigrant individuals and families. This article describes methods to recruit and retain recently arrived Hispanic families in longitudinal research and clinical practice. Barriers to continued engagement with recent-immigrant families include residential mobility, wariness toward authority figures (including researchers and practitioners), and unpredictable work schedules. These barriers can lead to challenges related to recruitment/engagement, logistics, establishing trust, and retention. This article describes decisions made, experiences, and lessons learned in a longitudinal study of Hispanic families in two cities. We also provide implications for clinical practice.